2020
DOI: 10.21203/rs.3.rs-51224/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Circadian variations in occurrence and the clinical presentation of Vestibular Migraine: A retrospective study

Abstract: Background: As a new clinical disease entity, vestibular migraine (VM) is considered to be the commonest cause of spontaneous episodic vertigo. This study is trying to explore the circadian variations in occurrence and the clinical presentation of VM.Methods: We conducted a retrospective study and identified female patients who fulfilled the 2012 International Headache Society-Bárány Society Criteria for VM. Population’s clinical data were collected, including onset time and descriptions of sensations experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Tang Yingchao [10] observed the clinical efficacy of nourishing blood and clearing the brain granules to prevent and treat vestibular migraine of blood deficiency and liver hyperactivity type. Liu Yin et al [11] used Chai Lian Ding Dazzling Granules to treat vestibular migraine with liver-stomach disharmony evidence with anxiety and depression state, and the results showed that it could effectively improve patients' vertigo symptoms and anxiety and depression. Wang Yang [12] used headache granules to conduct a clinical study on VM of the wind-yang upheaval type and found that the headache granules could reduce the patients' symptoms and improve their quality of life.…”
Section: Oral Chinese Medicine or Proprietary Chinese Medicinementioning
confidence: 99%
“…Tang Yingchao [10] observed the clinical efficacy of nourishing blood and clearing the brain granules to prevent and treat vestibular migraine of blood deficiency and liver hyperactivity type. Liu Yin et al [11] used Chai Lian Ding Dazzling Granules to treat vestibular migraine with liver-stomach disharmony evidence with anxiety and depression state, and the results showed that it could effectively improve patients' vertigo symptoms and anxiety and depression. Wang Yang [12] used headache granules to conduct a clinical study on VM of the wind-yang upheaval type and found that the headache granules could reduce the patients' symptoms and improve their quality of life.…”
Section: Oral Chinese Medicine or Proprietary Chinese Medicinementioning
confidence: 99%